Pengaruh Model Pembelajaran Value Clarification Technique terhadap Social Skill Mahasiswa - Fatma Sukmawati; Muhammad Jafar Nashir (IKIP PGRI Bojonegoro, 2021)
Abstract : Ideally, learning in the Education unit emphasizes three aspects, namely cognitive, affective and motoric. However, in reality, the affective aspect is still rarely considered, such as social skills. The purpose of this research is to find out whether there is a significant difference between the VCT model and the expository model on students' social skills. The research subjects were 100 students of the Islamic Religious Education study program at the Mambaul Ulum Institute, Surakarta. This type of research is a Quasi Experimental Research. The research design used a posttest only control group design where there were 2 research classes, namely the experimental class by applying the VCT model while the control class applying the expository model. The results of the study obtained a significance of 0.000, which means that there is a significant difference between the VCT t model and the expository model on students' social skills. Keyword: Value Clarification Technique model, Social SkillAbstrak : Idealnya, pembelajaran di satuan Pendidikan menekankan pada tiga aspek, yaitu kognitif, afektif dan motoric. Namun, pada kenyataanya, aspek afektif masih jarang diperhatikan seperti social skill. Tujuan dari dilaksanakanya penelitian ini yaitu mengetahui apakah ada perbedaan yang signifikan antara model VCT dengan model ekspositori terhadap social skill mahasiswa. Subjek penelitian adalah mahasiswa program studi Pendidikan Agama Islam Institut Mambaul Ulum Surakarta yang berjumlah 100 orang. Jenis penelitian ini merupakan Quasi Experimental Research. Adapun desain penelitiannya menggunkan posttest only control group design dimana terdapat 2 kelas penelitian, yaitu kelas eksperimen dengan menerapkan model VCT sedangkan kelas control menerapkan model eskpositori. Hasil penelitian diperoleh signifikansi yaitu 0,000, yang artinya terdapat perbedaan yang signifikan antara model VCT tdengan model ekspositori terhadap social skill mahasiswa. Kata kunci: Model Value Clarification Technique, Social Skill